Loyalitas Sebagai Akibat dari Kepuasan Pelanggan (Studi pada “Nanung Broiler” Di Kecamatan Majenang) - Hasan Muzaki (J-EBI: Jurnal Ekonomi Bisnis Islam, 2023)
AbstractThis research aims to investigate the relationship between customer satisfaction and customer loyalty with a focus on the "Nanung Broiler" kiosk in Majenang District. This research explores various indicators that influence customer loyalty, including aspects such as product taste, product quality, ease of communication, ability to borrow, kiosk location, order pick-up and delivery service, and stock availability. The research method used involves surveys, observations and interviews with customers who have subscribed to the "Nanung Broiler" kiosk.The research results show that these factors have a significant impact in influencing customer satisfaction and in turn, customer loyalty. "Nanung Broiler" customers tend to remain loyal because they feel the unique taste of the product, consistent product quality, ease of communicating with traders, the ability to borrow in emergency situations, strategic kiosk location, easy pick-up and drop-off service for orders, and good stock availability. always ready. Keywords: Customer Satisfaction, Customer Loyalty